Understanding pre-service teachers' mental health problems and resilience mechanisms during teaching practice at Mzumbe University. - Kihwele, Jimmy E.; Mmbando, Gladness; Mwego, Caleb (Journal of Adult Education in Tanzania ( JAET), 2026)
This article was sent to DPRS for publication